Cold dust and young starbursts: Spectral energy distributions of Herschel SPIRE sources from the HerMES survey - Rowan-Robinson, M.; Roseboom, I.; Vaccari, M.; Amblard, A.; Arumugam, V.; Auld, R.; Aussel, H.; Babbedge, T.; Blain, A.; Bock, J.; Boselli, A.; Brisbin, D.; et al. (Oxford University Press, 2010)
We present spectral energy distributions (SEDs) for 68 Herschel sources detected at 5s at 250, 350 and 500 µm in the HerMES SWIRE-Lockman field. We explore whether existing models for starbursts, quiescent star-forming galaxies and active galactic nucleus dust tori are able to model the full range of SEDs measured with Herschel. We find that while many galaxies ( 56 per cent) are well fitted with the templates used to fit IRAS, Infrared Space Observatory (ISO) and Spitzer sources, for about half the galaxies two new templates are required: quiescent ('cirrus') models with colder (10-20 K) dust and a young starburst model with higher optical depth than Arp 220. Predictions of submillimetre fluxes based on model fits to 4.5-24 µm data agree rather poorly with the observed fluxes, but the agreement is better for fits to 4.5-70 µm data. Herschel galaxies detected at 500 µm tend to be those with the highest dust masses. © 2010 The Authors. Journal compilation © 2010 RAS.